ANALISIS EFISIENSI KINERJA BANK SYARIAH MENGGUNAKAN DATA ENVELOPMENT DAN SHARIA MAQOSID INDEX TAHUN 2018-2020 - Hibatullah, Ilham; Supriyanto, Trisiladi; Syauqi Beik, Irfan (Universitas Ibn Khaldun Bogor, 2023)
Measurement of financial performance, including in Islamic banks, can be done by analyzing the ratios of financial statements. This analysis is needed to determine the extent to which banks have made certain achievements, especially in formulating strategic policies of an Islamic bank. This study aims to measure the efficiency of the performance of Islamic banks in Indonesia, Malaysia, Saudi Arabia, Pakistan, United Arab Emirates and Bahrain using the Data Envelopment approach. Analysis (DEA) and Sharia Maqashid Index (SMI), so that Islamic banks can continue to improve the quality of services and benefits to the community and can compete in the global financial industry.